2010
DOI: 10.1161/circresaha.109.209346
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Ischemia/Reperfusion Tolerance Is Time-of-Day–Dependent

Abstract: Rationale: Cardiovascular physiology and pathophysiology vary dramatically over the course of the day. For example, myocardial infarction onset occurs with greater incidence during the early morning hours in humans. However, whether myocardial infarction tolerance exhibits a time-of-day dependence is unknown. Objective: To investigate whether time of day of an ischemic insult influences clinically relevant outcomes in mice. Methods and Results: Wild-type mice were subjected to ischemia/reperfusion (I/R) (45 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
205
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 225 publications
(219 citation statements)
references
References 21 publications
11
205
2
1
Order By: Relevance
“…Furthermore, recent animal experimental data indicate increased susceptibility to cardiac ischemia/reperfusion at the sleep-wake transition that is mediated by the cardiomyocyte circadian clock, providing further support for the involvement of the circadian system in the timing of adverse cardiovascular events (35).…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, recent animal experimental data indicate increased susceptibility to cardiac ischemia/reperfusion at the sleep-wake transition that is mediated by the cardiomyocyte circadian clock, providing further support for the involvement of the circadian system in the timing of adverse cardiovascular events (35).…”
Section: Discussionmentioning
confidence: 85%
“…For instance, CCGs in the murine heart are involved in cardiac glucose and fatty acid metabolism (e.g., Dgat2 , Adpn , Ppp1cc 32), but also electrophysiology which results in oscillatory contractile properties 33 (e.g., Tcap 34 , Kv4.2, and KChIP2 35). Surprisingly, the cardiac‐specific clock not only drives rhythmic output under normal physiological conditions, but also under pathophysiological conditions as noted by its oscillating responsiveness to myocardial infarction mediated by oscillating phosphorylated Akt and GSK‐3 levels 36. In adipose tissue, the clock drives rhythmicity of lipogenesis and lipolysis, and even lipid release 37, via output genes such as Pnpla2 and Lipe 38.…”
Section: Tissue‐specific Circadian Clocks Influence Organ Physiologymentioning
confidence: 99%
“…6 Recently, experimental studies have shown that cardiomyocyte circadian clock affects the response of the heart to various stresses including ischemia/reperfusion by modulating multiple cardioprotective signaling pathways. 6,7 It is well known that onsets of adverse cardiac events, such as sudden cardiac death, 8 stroke, 9 and myocardial infarction increase from 6 AM. 10 The higher incidence of myocardial infarction during the latter part of the morning (6 AM to noon) can be explained by the combination of rise in arterial blood pressure, hormonal stimulation (β-adrenergic, cortisol), 11 hyperreactivity of platelets, 12 and shear stress resulting in atherosclerotic plaque disruption and thrombosis.…”
Section: Introductionmentioning
confidence: 99%